Investigação do papel receptor metabotrópico de glutamato do subtipo 5 na modulação de parâmetros inflamatórios e de obesidade em animais BACHD - Rebeca Priscila de Melo Santos (2019)
Obesity, as well as its comorbidities, represents a serious global public health problem. In obese patients, the adipose tissue presents characteristics of a low-grade chronic inflammatory state, which can increase the risk of developing comorbidities, such as: atherosclerosis, diabetes, insulin resistance. In this study was used BACHD mice, which have obesity phenotype. Moreover, BACHD mice show increased body weight and food intake, besides insulin and leptin resistance. Data from the literature have shown that negative modulation of metabotropic glutamate receptor subtype 5 (mGluR5) lead to decrease of: body weight, food intake and plasma concentrations of insulin and leptin. Thus, it was decided investigate whether mGluR5 has the ability to modulate obesity and also inflammatory parameters in BACHD mice. For that, crossing of BACHD and mGluR5 (mGluR5-/-) knockout mice were initially performed to obtain the groups: WT, mGluR5-/-, BACHD e BACHD/mGluR5-/-. The results showed that BACHD/mGluR5-/- group presented decreased body weight gain and lower visceral adiposity when compared to BACHD mice. Additionally, it was demonstrated that at 12 months of age, the concentration of adiponectin in epididymal adipose tissue of BACHD/mGluR5-/- animals was even higher than in BACHD mice. Moreover, the expression of leptin in the retroperitoneal adipose tissue and also in the average sum of visceral adipose tissues (VATs) of BACHD/mGluR5-/- group was lower than in BACHD mice. BACHD/mGluR5-/- group also had a higher ratio of adiponectin / leptin than BACHD mice in epididymal and mesenteric adiposo tissue and also in the average sum of VATs. Furthermore, at 12 months of age, BACHD/mGluR5-/- mice presented higher ratio of IL-10 / TNF as compared to BACHD group in the epididymal adipose tissue and also in the average sum of VATs. These results indicate that BACHD/mGluR5-/- animals have a lower inflammatory state in VATs, which suggests a lower cardiometabolic risk. Thus, the data obtained propose that the absence of mGluR5 seems to reduce weight gain and visceral adiposity in BACHD animals at 6 and 12 months. In addition, it is believed that at 12 months of age, this receptor may promoting an anti-inflammatory environment in the VATs.